Fostering Students’ Writing Skill through Peer Feedback Activity: A Case Study at UIN SMH Banten - Ila Amalia (English Education Department, 2018)
Students typically want their texts to be read, and in the classroom feedback from other student provides opportunities for them to see how others respond to their work and to learn from these responses. Since feedback is an important element in the process of writing, teacher must facilitate this kind of feedback to foster students’ writing skill. The present study concerned with the practice of peer feedback in the writing instruction, especially in writing an essay. More specifically this study investigated how peer feedback implemented in the classroom and how it influenced the students’ writing skill. The data were collected using two instruments, they were writing test and observation (using peer feedback format). From the result, it was found that students had gained more knowledge on the aspects of writing an essay and had made improvement on their writing skills especially in making the essay.